Program Edukasi Komunikasi Pintar untuk Meningkatkan Keterampilan Berkomunikasi Siswa SD Muhammadiyah 5 dan 11 Banjarmasin - Alya Nur Afifah Rahmi; Halimatus Sa’diah; Mewatia Silitonga; Muhammad Aris Fadillah; Virna Ramada Fitri; Sudirwo Sudirwo; Anna Nur Faidah (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2025)
This community service program aims to enhance the smart communication skills of young learners at SD Muhammadiyah 5 and 11 Banjarmasin through structured educational socialization and mentoring activities. The program was initiated in response to the low level of awareness among elementary school students regarding the importance of effective communication in supporting academic development and interpersonal relationships. The implementation consisted of several stages, including interactive socialization sessions, practical communication exercises, group discussions, and ice-breaking activities designed to build confidence and engagement. Evaluation results showed a notable improvement in students’ speaking, listening, and peer interaction abilities. Students demonstrated clearer articulation, better turn-taking in conversations, and increased willingness to participate in class activities. In addition, positive behavioral changes were observed, including improved self-confidence and more respectful communication patterns. These outcomes indicate that the smart communication-based character education approach is effective in strengthening students’ social and emotional development, particularly in early education environments. Overall, this program proves that targeted communication training can play a crucial role in fostering essential life skills among elementary school students.